2018
DOI: 10.1007/978-3-319-93387-0_32
|View full text |Cite
|
Sign up to set email alerts
|

Assentication: User De-authentication and Lunchtime Attack Mitigation with Seated Posture Biometric

Abstract: Biometric techniques are often used as an extra security factor in authenticating human users. Numerous biometrics have been proposed and evaluated, each with its own set of benefits and pitfalls. Static biometrics (such as fingerprints) are geared for discrete operation, to identify users, which typically involves some user burden. Meanwhile, behavioral biometrics (such as keystroke dynamics) are well-suited for continuous, and sometimes more unobtrusive, operation. One important application domain for biomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Given the significance of user de-authentication to prevent lunchtime attacks, different mechanisms have been proposed that aim at continuously establishing the user's presence/absence near the system. Kaczmarek et al [2] propose Assentication to profile user's sitting posture. In particular, Assentication installs 16 pressure sensors in an office chair to capture a hybrid biometric trait by combining user's behavioral and physiological characteristics.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the significance of user de-authentication to prevent lunchtime attacks, different mechanisms have been proposed that aim at continuously establishing the user's presence/absence near the system. Kaczmarek et al [2] propose Assentication to profile user's sitting posture. In particular, Assentication installs 16 pressure sensors in an office chair to capture a hybrid biometric trait by combining user's behavioral and physiological characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…If the user wants to leave her computer for whatever reason during this period, her currently active session must be locked/logged out; especially in shared workspace settings. Failure to do so can lead to lunchtime attacks [1], [2], where an adversary (typically an insider) gains access to the user's running session and engages in potentially undesirable activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FADEWICH [8] instruments an office with position sensors to detect whether the users are sitting at their desks. Assentication [22] detects user presence through pressure sensors in the chair cushion. Whereas, [10] instruments a chair with BLE beacons to detect whether the user is currently sitting.…”
Section: A De-authenticationmentioning
confidence: 99%
“…Besides using human-smartphone interactions, multimodal authentication also uses other factors. T. Kaczmarek et al [27] investigated a new hybrid biometric based on a human users seated posture pattern in an average office chair over the course of a typical workday. Their experimental results on a population of 30 users showed that the posture pattern biometric can capture a unique combination of physiological and behavioral traits and can authenticate the users with 91% of accuracy.…”
Section: Other Multimodal Authenticationmentioning
confidence: 99%